2016
DOI: 10.1038/labinvest.2015.161
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial theory applied to the neurotoxicity of paraquat and paraquat-induced mechanisms of developing Parkinson's disease

Abstract: Laboratory studies involving repeated exposure to paraquat (PQ) in different animal models can induce many of the pathological features of Parkinson's disease (PD), such as the loss of dopaminergic neurons in the nigrostriatal dopamine system. Epidemiological studies identify an increased risk of developing PD in human populations living in areas where PQ exposure is likely to occur and among workers lacking appropriate protective equipment. The mechanisms involved in developing PD may not be due to any single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 121 publications
1
50
0
Order By: Relevance
“…This agrochemical is very hydrosoluble (620 g/L of solubility in water at 25 °C) because of the presence of cationic charge on the molecule, which eradicates plants by interrupting photosynthesis [1]. Nevertheless, paraquat is very dangerous for health such as dermal exposure [5], respiratory failure [6], pulmonary fibrosis [7,8], neurotoxicity [9], damage of digestive apparatus [1] and Parkinson's disease [10,11]. The paraquat amount of 35 mg/kg displays lethal dose for human being owing to European standards [12].…”
Section: Introductionmentioning
confidence: 99%
“…This agrochemical is very hydrosoluble (620 g/L of solubility in water at 25 °C) because of the presence of cationic charge on the molecule, which eradicates plants by interrupting photosynthesis [1]. Nevertheless, paraquat is very dangerous for health such as dermal exposure [5], respiratory failure [6], pulmonary fibrosis [7,8], neurotoxicity [9], damage of digestive apparatus [1] and Parkinson's disease [10,11]. The paraquat amount of 35 mg/kg displays lethal dose for human being owing to European standards [12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of paraquat in drinking water sources may represent a serious threat to human health, due to its acute toxicity level, which was the main reason that led to its ban in several countries [9]. In addition, this herbicide has been linked to several diseases in humans, including Parkinson’s disease [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a lot of evidences indicated that aggregated α-syn could be facilitated by many environmental neurotoxins. Agrochemicals such as paraquat(PQ), rotenone, maneb were believed to be important factors that gave rise to the accumulation and aggregation of α-syn and could be the contributors to the occurrence and development of PD [97][98][99][100]. Moreover, heavy metals have also been paid more attention, because α-syn has multiple binding sites of metal [101].…”
Section: α-Synuclein Aggregation and Parkinson Diseasementioning
confidence: 99%